2004
DOI: 10.1007/s00395-004-0500-9
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase gene transfer restores endothelium–dependent relaxations and attenuates lesion formation in carotid arteries in apolipoprotein E–deficient mice

Abstract: Nitric oxide (NO) and monocyte chemoattractant protein-1 (MCP-1) exert partly opposing effects in vascular biology. NO plays pleiotropic vasoprotective roles including vasodilation and inhibition of platelet aggregation, smooth muscle cell proliferation, and endothelial monocyte adhesion, the last effect being mediated by MCP-1 downregulation. Early stages of arteriosclerosis are associated with reduced NO bioactivity and enhanced MCP-1 expression. We have evaluated adenovirus-mediated gene transfer of human e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…NO is a bifunctional endothelial vasodilator that suppresses platelet aggregation, leucocyte adhesion and proliferation of vascular smooth muscle cells. However, excessive NO can react with superoxide anions and produce strong oxidizing peroxynitrite anions (ONOO‐), which can further result in lipid peroxidation and direct damage to endothelial cells . As shown in this study, compared with the blank group, PI3K, Akt and eNOS mRNA levels were up‐regulated in the miR‐138 inhibitor group but were down‐regulated in the miR‐138 mimic and LY294002 groups.…”
Section: Discussionmentioning
confidence: 53%
“…NO is a bifunctional endothelial vasodilator that suppresses platelet aggregation, leucocyte adhesion and proliferation of vascular smooth muscle cells. However, excessive NO can react with superoxide anions and produce strong oxidizing peroxynitrite anions (ONOO‐), which can further result in lipid peroxidation and direct damage to endothelial cells . As shown in this study, compared with the blank group, PI3K, Akt and eNOS mRNA levels were up‐regulated in the miR‐138 inhibitor group but were down‐regulated in the miR‐138 mimic and LY294002 groups.…”
Section: Discussionmentioning
confidence: 53%
“…NO and MCP-1 exert partly opposing effects in vascular biology. NO plays a pleiotropic vasoprotective role including vasodilatation and inhibition of platelet aggregation, smooth muscle cell proliferation and endothelial monocyte adhesion, the last effect being mediated by MCP-1 down regulation [31]. In our study, polymorphic alleles of eNOS and MCP1 genes were shown to have different alterations in cirrhotic patients compared with controls.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, aortas from young apoE -/- mice fed a regular chow diet exhibit normal eNOS expression and normal dilation responses to ACh [63,64]. However, transfer of the eNOS gene into apoE -/- mice carotid arteries in vivo results in increased eNOS expression levels and normalized relaxation responses to ACh [72]. Interestingly, apoE -/- mice fed a Western-type diet exhibit increased vascular ET-1 production, reduced endothelial NO release, and impaired endothelium-dependent relaxation, which are all normalized by chronic blockage of the ET A receptor [68].…”
Section: Endothelial Function and Dysfunction In The Apoe-/- Mousementioning
confidence: 99%